Serum markers of deranged myocardial collagen turnover: their relation to malignant ventricular arrhythmias in cardioverter-defibrillator recipients with heart failure - Flevari,P.; Theodorakis, G; Leftheriotis, D; Kroupis, C.; Kolokathis,F.; Dima, K.; Anastasiou-Nana, M.; Kremastinos, D. (Am.Heart J., 2012)
BACKGROUND: Pathologic collagen remodeling has been involved in the occurrence of ventricular arrhythmias and sudden cardiac death in heart failure. The aim of the study was to investigate the relationship between malignant ventricular arrhythmias and cardiac collagen turnover indexes, expressing specific types of derangement in collagen physiology, in stable patients with an implantable cardioverter-defibrillator (ICD). METHODS: Seventy-four patients with an ICD and heart failure were studied. They had coronary artery disease (n = 42) or dilated cardiomyopathy, New York Heart Association classes I and II, and left ventricular ejection fraction 29% +/- 1%. An ICD had been implanted for secondary (n = 36) or primary prevention of sudden cardiac death. We assessed (1) markers of collagen types I and III synthesis and their ratio: procollagen type I carboxyterminal peptide (PICP), procollagen type III aminoterminal peptide (PIIINP), and PICP/PIIINP; (2) markers of collagen degradation, degradation inhibition, and their ratio: matrix metalloproteinase 9 (MMP-9), tissue inhibitor of matrix metalloproteinase (TIMP) 1 (TIMP-1), and MMP-9/TIMP-1. Patients were prospectively followed up for 1 year. The number of episodes necessitating appropriate interventions for ventricular tachyarrhythmias (>170 beat/min) was related to the assessed parameters. RESULTS: Multivariate analysis revealed a significant relation between the number of tachyarrhythmic episodes and MMP-9/TIMP-1 (P = .007), PICP/PIIINP (P = .007), and ejection fraction (P = .04). No other significant relation was observed between arrhythmias and the remaining parameters. CONCLUSION: In heart failure, biochemical markers indicative of a deranged equilirium in myocardial collagen deposition/degradation and collagen I/III synthesis are related to ventricular arrhythmogenesis. Further studies are needed to investigate their predictive ability
Keywords: Biomarkers; biosynthesis; Blood; Cardiomyopathy,Dilated; Collagen Type I; Collagen Type III; Coronary artery disease; Death,Sudden,Cardiac; Defibrillators,Implantable; Female; Follow-Up Studies; Greece; Heart failure; Humans; Interleukin-6; Male; Matrix Metalloproteinase 9; metabolism; Middle Aged; Myocardium; Natriuretic Peptide,Brain; Peptide Fragments; physiology; prevention & control; Procollagen; Stroke Volume; Tachycardia,Ventricular; therapy; Tissue Inhibitor of Metalloproteinase-1